The management of HIV positive patients using a CD8/38 flow cytometry assay as an alternative to viral load testing - Moodley, Keshendree (My University, 2011)
BACKGROUND: Human Immunodeficiency Virus (HIV) is a global epidemic with growing numbers of people on highly active anti‐retroviral therapy (HAART) programmes. Effectiveness of treatment needs to be monitored to ensure the uncompromised well being of patients. This is currently done using both Viral Load (VL) and CD4 cell counts for HAART initiation and follow‐up. Although VL is the best predictor of disease progression it is often too expensive for monitoring patients in resource‐limited settings. There is thus a need for a cheaper, more accessible alternative to monitor long term patient response to therapy. METHODS: This study evaluated the use of a recently described flow cytometric assay of CD38 expression (previously developed at the Johannesburg Flow Cytometry Reference Laboratory) in a cohort of HIV+ patients failing 1st line therapy, who were subsequently enrolled onto 2nd line HAART. CD38 and CD8 were “piggy ‐backed” onto the PLG/CD4 protocol and mean fluorescence intensity (MFI) of the CD8/38 expression was monitored longitudinally. Patterns of CD38 expression were compared to 1st line treatment observations to establish equivalence in the predictive power of CD38 expression of fluctuation in viral load on 2nd line treatment patients. In addition, the effect of sample age on assay accuracy was tested before implementation of the CD38 assay at a secondary testing site. RESULTS: The patterns observed in the cohort of 2nd line therapy patients mirrored patterns previously seen in 1st line therapy with 55% of patients showing a continuous decline in CD38 MFI that mimicked changes in VL. The remaining 33% of patients had non‐specific increases in CD38 MFI without concurrent increases in VL and one patient showed irregular VL and CD38 MFI (non‐responder). The CD38 assay showed acceptable accuracy and reproducibility up to 48 hours after venesection (%CV<5%). Implementation at the secondary testing site was successful with 98% similarity (%CV<5%) compared to the reference laboratory. CONCLUSION: CD38 monitoring of 2nd line therapy patients showed comparable patterns to observations in 1st line therapy patients. The assay proved stable over time and easy to implement at another PLG/CD4 testing facility. As such, the CD38 assay offers a cost‐effective, reliable real time supplementary test to long‐term VL monitoring of HIV infected patients on the national ART programme.
MSc (Med), Faculty of Health Sciences, University of the Witwatersrand, 2011
Keywords: HIV-1; flow cytometry; HIV patient management